Visualization and characterization of tobacco mosaic virus movement protein binding to single-stranded nucleic acids. - Citovsky, V (1992)
Cell-to-cell spread of tobacco mosaic virus (TMV) is presumed to occur through plant intercellular connections, the plasmodesmata. Viral movement is an active process mediated by a specific virus-encoded P30 protein. P30 has at least two functions, to cooperatively bind single-stranded nucleic acids and to increase plasmodesmatal permeability. Here, we visualized P30 complexes with single-stranded DNA and RNA. These complexes are long, unfolded, and very thin (1.5 to 2.0 nm in diameter). Unlike TMV virions (300 x 18 nm), the complexes are compatible in size with the P30-induced increase in plasmodesmatal permeability (2.4 to 3.1 nm), making them likely candidates for the structures involved in the cell-to-cell movement of TMV. Mutational analysis using single and double deletion mutants of P30 revealed three regions potentially important for the protein function. Amino acid residues 65 to 86 possibly are required for correct folding of the active protein, and the regions between amino acid residues 112 to 185 and 185 to 268 potentially contain two independently active single-stranded nucleic acid binding domains designated binding domains A and B, respectively.